IgA EGFR antibodies mediate tumour killing in vivo. Issue 8 (5th August 2013) - Boross, Peter; Lohse, Stefan; Nederend, Maaike; Jansen, Johannes Hendrik Marco; van Tetering, Geert; Dechant, Michael; Peipp, Matthias; Royle, Louise; Liew, Li Phing; Boon, Louis; van Rooijen, Nico; Bleeker, Wim K.; et al.
<x xml:space="preserve">Abstract</x> Currently all approved anti‐cancer therapeutic monoclonal antibodies (mAbs) are of the IgG isotype, which rely on Fcgamma receptors (FcγRs) to recruit cellular effector functions. In vitro studies showed that targeting of FcαRI (CD89) by bispecific antibodies (bsAbs) or recombinant IgA resulted in more effective elimination of tumour cells by myeloid effector cells than targeting of FcγR. Here we studied the in vivo anti‐tumour activity of IgA EGFR antibodies generated using the variable sequences of the chimeric EGFR antibody cetuximab. Using FcαRI transgenic mice, we demonstrated significant in vivo anti‐tumour activity of IgA2 EGFR against A431 cells in peritoneal and lung xenograft models, as well as against B16F10‐EGFR cells in a lung metastasis model in immunocompetent mice. IgA2 EGFR was more effective than cetuximab in a short‐term syngeneic peritoneal model using EGFR‐transfected Ba/F3 target cells. The in vivo cytotoxic activity of IgA2 EGFR was mediated by macrophages and was significantly decreased in the absence of FcαRI. These results support the potential of targeting FcαRI for effective antibody therapy of cancer.